Recombinant Tissue Factor as Substitute for Conventional Thromboplastin in the Prothrombin Time Test - Tripodi, Armando; Arbini, Arnaldo; Chantarangkul, Veena; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1992)
Relipidated recombinant tissue factor (r-TF) has been assessed in comparison with conventional rabbit brain thromboplastin (Manchester Reagent) for its suitability for measurement of prothrombin time (PT). The International Sensitivity Index (ISI) of r-TF calibrated against the International Reference Preparation BCT/253 (human plain) was found to be 0.96 and 1.12 with instrumental and manual techniques. Our study of plasmas from patients with congenital deficiencies of clotting factors covering a wide range of severity demonstrates that r-TF is able to detect even minor deficiencies of factors involved in the extrinsic and common coagulation pathways. Patients with liver diseases were correctly diagnosed with a prevalence of abnormal results comparable for both reagents. Between-assay reproducibility expressed as coefficient of variation was 2.3 % and 3.9 % at normal and abnormal PT levels.In conclusion, our evaluation shows that relipidated r-TF possesses the necessary requisites of sensitivity, diagnostic accuracy and reproducibility which make it a suitable candidate for PT determination both for monitoring oral anticoagulant therapy and diagnosing congenital and acquired clotting factor deficiencies. Moreover, being a highly defined reagent it may constitute a step forward in the standardization of PT testing.